2012
DOI: 10.1007/s00439-012-1249-0
|View full text |Cite
|
Sign up to set email alerts
|

Variants in GATA4 are a rare cause of familial and sporadic congenital diaphragmatic hernia

Abstract: Congenital diaphragmatic hernia (CDH) is characterized by incomplete formation of the diaphragm, occurring as either an isolated defect or in association with other anomalies. Genetic factors including aneuploidies and copy number variants are important in the pathogenesis of many cases of CDH, but few single genes have been definitively implicated in human CDH. In this study, we used whole exome sequencing (WES) to identify a paternally inherited novel missense GATA4 variant (c. 754C>T, p. R252W) in a familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 29 publications
2
76
0
Order By: Relevance
“…This would primarily be consistent with the GATA4 variant in this family, because previous studies have shown that GATA4 variants, though they are occasionally accompanied by extra‐cardiac features such as 46,XY DSD6, 7 and congenital diaphragmatic hernia,14 usually lead to isolated CHDs (primarily ASD2). However, lack of extra‐cardiac features is not a common finding in CHDs in general.…”
Section: Discussionsupporting
confidence: 86%
“…This would primarily be consistent with the GATA4 variant in this family, because previous studies have shown that GATA4 variants, though they are occasionally accompanied by extra‐cardiac features such as 46,XY DSD6, 7 and congenital diaphragmatic hernia,14 usually lead to isolated CHDs (primarily ASD2). However, lack of extra‐cardiac features is not a common finding in CHDs in general.…”
Section: Discussionsupporting
confidence: 86%
“…Mutations in GATA4 , a paralogue of GATA6 , have recently been identified in only one of a cohort of 96 patients with CDH,5 so we reasoned that a larger cohort might be needed to find additional patients with GATA6 mutations. We took advantage of a recently described high throughput targeted sequencing approach,8 using MIPs to screen a cohort of 357 patients with CDH (clinical information in online supplementary table S4), 83 of whom overlapped with those Sanger sequenced.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely due to the historically high mortality in CDH, resulting in very few multiplex families amenable to traditional linkage analysis. De novo rare variants have been identified as a cause of sporadic diseases with decreased reproductive fitness,4 and a pathogenic de novo variant in GATA4 was recently identified as a cause of CDH 5. Allen et al identified a de novo c.1516+4A>G mutation in GATA6 in a patient with pancreatic agenesis and CDH 6.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genomic sequence analysis of patients with CDH, correlated with gene expression studies in the developing mouse diaphragm, has identified a growing list of candidate genes implicated in the pathogenesis of CDH (14,16,(20)(21)(22)(23). Among them are Pbx genes that encode homeodomain-containing transcription factors best known to act as Hox cofactors (24,25).…”
Section: Introductionmentioning
confidence: 99%